Effect of preoperative education about spinal anesthesia on anxiety and postoperative pain in parturients undergoing elective cesarean section: A randomized controlled trial - Anila K Kalliyath; Sara V Korula; Anna Mathew; Saramma P Abraham; Mini Isac (Wolters Kluwer Medknow Publications, 2019)
Background: Preoperative anxiety is a common problem in all patients. The reason could be incomplete information regarding the anesthesia and surgical procedure. Cesarean section (CS) is a common surgery and treatment of postoperative pain after CS continues to be an ongoing challenge. Aim: The present study was carried out to assess if preoperative education with a handout about spinal anesthesia can reduce anxiety and postoperative pain in parturients undergoing CS under spinal anesthesia. Methods and Materials: We randomized 64 parturients into two equal groups; study (Group A) and control group (Group B). The study group was given a handout and a structured education about spinal anesthesia. The control group was given routine preoperative information. The Amsterdam preoperative anxiety and information scale (APAIS) was used to measure anxiety preoperatively and visual analogue scale (VAS) for pain at 5 h and 24 h postoperatively. Statistical Analysis: The two groups were compared using Student's t test and non-parametric Wilcoxon-Mann-Whitney U test. Result: The median difference in preoperative anxiety scores (APAIS) in the two groups was found to be 8.00 (P < 0.001), which was significant statistically. The median value of postoperative pain analyzed using VAS after giving education, at 5 h was significantly reduced in Group A (5.00) as compared to Group B (9.00). The median value of VAS score at 24 h was significantly different in both groups. It was 1.0 in Group A, whereas the same was 5.50 in Group B (P <.00). The median difference in hours in the duration of analgesia between the two groups was 0.62, which was not significant statistically (P < 0.10). Conclusion: A planned preoperative education and handout with details about spinal anesthesia can have a significant impact on reducing the preoperative anxiety and the postoperative pain in parturients undergoing elective CS under spinal anesthesia.